Asia Pacific security values and identity - Buszynski, Leszek (RoutledgeCurzon security in Asia series, 2004)
The theme of this book is that security is not just about defence from external attack, but embraces the protection of identity and values which cultures regard as important, and which they may regard as worth fighting for. It examines Asia Pacific security from the perspective of the values and identities of China, Japan, the Koreas and the USA.